Strategi Komunikasi Krisis Zulkifli Hasan Menyikapi Isu Deforestasi dan Banjir Sumatra - Mazka Hauzan Naufal; Ismi Dwi Astuti Nurhaeni; Andre Noevi Rahmanto (Jurnal Audiens, 2026)
This study analyzes Zulkifli Hasan’s crisis communication strategies in response to public attribution of responsibility for the 2025 Sumatra flood disasters, which were linked to his past policies. Utilizing the Situational Crisis Communication Theory (SCCT) framework, this research identifies that although the crisis is categorized as a preventable crisis, which theoretically necessitates a full apology, the subject instead implemented a combination of self-defense strategies. The research findings reveal three primary tactics: (1) Denial through the “attack the accuser" tactic to discredit the Harrison Ford interview video as a biased and modified film product; (2) Diminish using a "democratic surplus" narrative to shift ministerial responsibility to the structural failures of regional autonomy during the Reformation era; and (3) Bolstering via "ingratiation" by associating himself with the legitimacy of President Prabowo Subianto’s administration and employing theological emphasis to assert personal integrity. The novelty of this research lies in its analytical focus on managing reputational crises triggered by the re-contextualization of past digital footprints within a long-form podcast narrative format, a dimension that addresses a gap in crisis communication studies previously dominated by short-form social media platforms. This study suggests that future research utilize big data-based sentiment analysis methods to quantitatively measure the effectiveness of such rhetoric in shifting public perception.